Shadows and Lights: Perspectives of Training and Education in Neurosurgery for Undergraduate Students - Zoli, Matteo; Zenesini, Corrado; Bassani, Gemma; Colangelo, Andrea; Fayel, Elad; Labanca Lima, Giullia; Maestri, Matteo; Pinto, Giuseppe; Scibilia, Antonino; Conti, Alfredo; Mazzatenta, Diego (Frontiers in Surgery, 2022)
Introduction. Neurosurgical education should start during medical school to involve more studentsas possible, favoring the recruitment of the most prepared and motivated ones and spreading this subject to the future medical generations. Despite multiple investigations, a dedicated educational plan does not exist. Aim of this study is to assess the undergraduates’ interest, needs and perception of this subject. Materials and Methods.A survey was electronically proposed to medical students of the University of Bologna. The survey was structured to collect demographic data of the participants, and to explore their personal interest in neurosurgery, their consideration of its importance in medical school, their opinions about the role of this subject in medical education, their needs in this training and, the usefulness of this subject for their future career. Results. A total of 156 students participated in the survey. Interest in neurosurgery was shown by 76 (48.7%) participants, however, this subject was also perceived as intimidating by 86 (55.1%). The attending of the first 2 years of medical school (p<0.02), previous interest in neuroscience (p<0.01) and in a surgical subject (p<0.01) were the factors associated with a greater interest in this subject. Neurosurgery should be included in all students’ education, according to 117 (75.0%) participants and practical operating room training should involve all students, according to 96 (61.5%). The most effective learning methods were considered internship (134, 85.9%), followed by participation in meetings or seminars (113, 72.4%). Online seminars were considered useful by 119 participants (76.3%). Neurosurgery was assessed as a potentially interesting career by 99 students (63.5%), who also considered that it can increase their preparation for other subjects (116, 74.4%). Conclusions. Neurosurgery was positively considered by medicals students, who, however, also perceived it as intimidating and hardly approachable. Demonstration that knowledge of neurosurgical concepts can improve their preparation also in general medicine settings and, not only in the field of neuroscience , can be useful to promote their interest toward this subject. A combination of lectures and practical internships is considered an effective learning method, which can be fruitfully associated with new technologies.